THE IMPACT OF GUT MICROBIOTA ON RECURRENT APHTHOUS STOMATITIS - Mihaela Paula Toader; Oana Mihaela Condurache Hritcu; Cristina Popa; Ana Maria Sciuca; Bianca Andreea Onofrei; Stefan Vasile Toader (Romanian Dental Association for Education, 2024)
Recurrent Aphthous Stomatitis (RAS) is a prevalent oral mucosal disorder characterized by recurring painful ulcers. The pathogenesis of RAS remains incompletely understood, but emerging evidence suggests a significant link between gut microbiota and the development of RAS. This review aims to explore the existing literature on the interplay between gut microbiota and RAS, focusing on how intestinal dysbiosis may influence the onset and severity of RAS. We discuss the role of gut microbiota in immune modulation, the breakdown of oral tolerance, and the possible pathways through which gut bacteria can affect oral health. Additionally, we examine the impact of diet, antibiotics, and probiotics on the gut microbiota and, subsequently, on RAS. The review concludes with potential therapeutic strategies targeting gut microbiota to manage and prevent RAS, paving the way for novel interventions in this field.